Perceived Benefits and Perceived Barriers Toward Satisfaction of JKN-KIS Kidney Failure Patients with a Systems Approach - Riza, Yeni (Universitas Baiturrahmah, 2024)
Indonesia entered the era of National Health Insurance (JKN) in January 1, 2014. Due to the limited availability of hemodialysis services and the fact that the majority of patients with chronic kidney failure are unable to afford them, there is a difference before the JKN when patients with chronic kidney failure attempt to find alternative treatments prior to beginning hemodialysis. This study analyzes perceived benefits and perceived barriers to satisfaction of JKN-KIS kidney failure patients with a systems approach. The design of this study is a mixed method, a quantitative combination using CSI followed by a chi-square test and qualitative with a systematic approach that focuses on collecting and analyzing to obtain comprehensive data for the period January-August 2021. Based on the CSI method, it was found that the satisfaction rate was 80.1%, which means very satisfied. Chi-square analysis shows that perceived benefit is significantly associated with satisfaction (p-value<0.05), with adjusted OR=9,000 (95%CI: 3,573-22,673), as well as perceived barrier with adjusted OR=8,800 (95%CI: 1,575-49,162). Changes in behavior in respondents are influenced by a belief in perceived benefits and obstacles. These changes will be supported by the discovery of threat perception, severity and high severity, as well as the successful socialization received by respondents.